Optimal Screw Trajectory for Percutaneous Screw Fixation of Sanders Type ⅡC Calcaneal Fractures: A Finite Element Analysis - Peng, Yang; Luo, Gang; Ni, Weidong (Journal of Contemporary Medical Practice, 2025)
Background: Percutaneous screw fixation has been widely used to treat calcaneal fractures, but the optimal screw configuration is still unclear. In this study, finite element analysis was used to explore the optimal screw fixation. Methods: Mimics 21.0 software was used to process the ankle CT of a healthy subject and extract a three-dimensional model of the calcaneus. After optimizing the model using Geomagic Wrap 2021, the SandersⅡC fracture model was constructed in SolidWorks 2022 and four internal fixation methods with different screw directions were designed to simulate the internal fixation of the fracture. Finally, the finite element analysis was completed in ANSYS Workbench 2022 R1. Results: The maximum stress of screw and bone and the maximum displacement of fracture fragment in the study group and control groups 1 were significantly smaller than those in the control groups 2 and 3. Conclusion: The screw configuration of study group and control group 1 (two transverse screws to fix the articular surface fracture fragment, one longitudinal screw fixed from the calcaneal tuberosity to the calcaneal anterior process, and one longitudinal screw fixed from the calcaneal tuberosity to the sustentaculum talus) can obtain the best biomechanical fixation effect.